Dental pulp stem cell-derived exosomes suppress M1 macrophage polarization through the ROS-MAPK-NFκB P65 signaling pathway after spinal cord injury - Chao Liu; Fanqi Hu; Genlong Jiao; Yue Guo; Pan Zhou; Yuning Zhang; Zhen Zhang; Jing Yi; Yonggang You; Zhizhong Li; Hua Wang; Xuesong Zhang (Journal of Nanobiotechnology, 2022)
Abstract Stem cell-derived exosomes have recently been regarded as potential drugs for treating spinal cord injury (SCI) by reducing reactive oxygen species (ROS) and suppressing M1 macrophage polarization. However, the roles of ROS and exosomes in the process of M1 macrophage polarization are not known. Herein, we demonstrated that ROS can induce M1 macrophage polarization and have a concentration-dependent effect. ROS can induce M1 macrophage polarization through the MAPK-NFκB P65 signaling pathway. Dental pulp stem cell (DPSC)-derived exosomes can reduce macrophage M1 polarization through the ROS-MAPK-NFκB P65 signaling pathway in treating SCI. This study suggested that DPSC-derived exosomes might be a potential drug for treating SCI. Disruption of the cycle between ROS and M1 macrophage polarization might also be a potential effective treatment by reducing secondary damage. Graphical Abstract